Considering canal pool resonance in controller design - Clemmens, Albert J., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2010)
The Integrator-Delay (ID) model (Schuurmans et al 1999) is a simple model of canal response that is used for design of various canal controllers. It describes the change in water depth at the downstream end of a canal pool as a function of flow changes at the upstream and downstream gates. Canal pools are characterized by a Delay time and a backwater surface area (Integrator). This model works very well for canal pools where water is flowing under normal depth conditions for a portion of the length, or where there are drops. For canal pools where the upstream flow depth is influenced by the downstream flow depth (that is, where canal pool is under backwater) the ID model often does not properly represent the water-level response. Changes in gate flows often cause a step change in water level. Schuurmans (1997) and Miltenburg (2008) propose the use of filters to account for this step change (ID-F), where the filter effectively causes a delay in response. Litrico and Fromion (2004) proposed the IDZ model, where a gate flow change causes a step change in downstream water level, after which the water level response follows the integrator of the ID model. The IDZ model does not fully account for resonance. An IDZ model with Filtering (IDZ-F) is proposed to account for additional resonance. In this paper, we compare the resulting water level response when the ID-F and IDZ-F models are used to design canal controllers for canal pools under backwater. It is shown that controllers designed with the IDZ-F model provide slightly better control than when designed with the ID-F model, although differences are not significant.
Meeting irrigation demands in a water-challenged environment
Canal pool resonance
Presented at Meeting irrigation demands in a water-challenged environment: SCADA and technology: tools to improve production: a USCID water management conference held on September 28 - October 1, 2010 in Fort Collins, Colorado.